Maize Starch-Branching Enzyme Isoforms and Amylopectin Structure. In the Absence of Starch-Branching Enzyme IIb, the Further Absence of Starch-Branching Enzyme Ia Leads to Increased Branching - Yao, Yuan (American Society of Plant Biologists, 2004)
Previous studies indicated that the deficiency of starch-branching enzyme (SBE) Ia in the single mutant sbe1a∷Mu (sbe1a) has no impact on endosperm starch structure, whereas the deficiency of SBEIIb in the ae mutant is well known to reduce the branching of starch. We hypothesized that in maize (Zea mays) endosperm, the function of SBEIIb is predominant to that of SBEIa, and SBEIa would have an observable effect only on amylopectin structure in the absence of SBEIIb. To test this hypothesis, the mutant sbe1a was introgressed into lines containing either wx (lacking the granule-bound starch synthase GBSSI) or ae wx (lacking both SBEIIb and GBSSI) in the W64A background. Both western blotting and zymogram analysis confirmed the SBEIa deficiency in sbe1a wx and sbe1a ae wx, and the SBEIIb deficiency in ae wx and sbe1a ae wx. Using zymogram analysis, no pleiotropic effects of sbe1a genes on SBEIIa, starch synthase, or starch-debranching enzyme isoforms were observed. High-performance size exclusion chromatography analysis shows that the chain-length profiles of amylopectin as well as β-limit dextrin were indistinguishable between wx and sbe1a wx, whereas significant differences for both were observed between ae wx and sbe1a ae wx, suggesting an effect of SBEIa on amylopectin biosynthesis that is observable only in the absence of SBEIIb. The amylopectin branch density and the average number of branches per cluster were both higher in endosperm starch from sbe1a ae wx than from ae wx. These results indicate possible functional interactions between SBE isoforms that may involve enzymatic inhibition. Both the cluster repeat distance and the distance between branch points on the short intracluster chains were similar for all genotypes however, suggesting a similar pattern of individual SBE isoforms in cluster initiation and the determination of branch point location.